Back to Predicting Future Educational Attainment: Two New Measures and Their Validity - Stephen L. Morgan (Socius)
Through an analysis of the U.S. Department of Education’s High School Longitudinal Study, this article offers models of educational attainment that assess the explanatory value of four complementary measures. On the 11th grade survey instrument, questions are offered on both educational aspirations and expectations, which is the first time since 1972 that both questions have been asked on a comparable longitudinal survey in the United States. The instrument then poses two questions that elicit probabilistic forecasts of future educational attainment, which have never been asked of high school students on such surveys. The empirical analysis in this article shows that the first two questions affirm the continuing relevance of the status socialization theory of educational attainment, and related empirical modeling that has been shaped by it, but the two new questions provide support for embracing more recent models that focus on belief formation and uncertainty.